PELABELAN TOTAL SUPER TRIMAGIC SISI PADA BEBERAPA GRAF - Robertus Heri Utomo; Heru Tjahjana; Bambang Irawanto; Lucia Ratnasari (Diponegoro University, 2018)
This paper is addressed to discuss the edge super trimagic total labeling on some graphs which are corona, double ladder, quadrilateral snake and alternate triangular snake. The main results are the edge super trimagic total label for these graphs. Furthermore, it was prove that corona is a graph with edge super trimagic total labeling, a double ladder with odd ladder is graph with edge super trimagic total labeling, quadrilateral snake is a graph with edge super trimagic total labeling and finally an alternate triangular snake with odd ladder is graph with edge super trimagic total labeling.